2022
DOI: 10.3390/solar2020014
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics on Solar Dish in a Concentrated Solar Power: A Bibliometric Review

Abstract: Concentrated solar power is an alternative renewable energy technology that converts solar energy into electrical energy by using a solar concentrator and a solar receiver. Computational fluid dynamics have been used to numerically design concentrated solar power. This is a powerful numerical analysis approach that is widely used in energy and environmental engineering applications. In this paper, we review previous work on the applications of computational fluid dynamics in the design of concentrated solar po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…This consisted of a map in which the colors indicate the degree of correlation between two variables under the measure of a statistical metric of chi-square co-occurrence. On the numerical scale, the value of −10 showed that the observed result of co-occurrence is 10 times lower than expected, on the other hand, the value of 10 indicated that the observed co-occurrence is 10 times higher than the expected value [ 39 ]. Additionally, the matrix presented a negative relationship through the blue cells, while the red cells meant a strong relationship; likewise, the white cells indicated that the variables had no relationship (neutrality) [ 40 ].…”
Section: Bibliometric Analysis Of Deproteinized Natural Rubbermentioning
confidence: 99%
“…This consisted of a map in which the colors indicate the degree of correlation between two variables under the measure of a statistical metric of chi-square co-occurrence. On the numerical scale, the value of −10 showed that the observed result of co-occurrence is 10 times lower than expected, on the other hand, the value of 10 indicated that the observed co-occurrence is 10 times higher than the expected value [ 39 ]. Additionally, the matrix presented a negative relationship through the blue cells, while the red cells meant a strong relationship; likewise, the white cells indicated that the variables had no relationship (neutrality) [ 40 ].…”
Section: Bibliometric Analysis Of Deproteinized Natural Rubbermentioning
confidence: 99%